Single-Cell Sequencing Reveals the Novel Role of Ezh2 in NK Cell Maturation and Function - Yu, Minghang; Su, Ziyang; Huang, Xuefeng; Wang, Xi (Frontiers in Immunology, 2021)
Natural killer (NK) cells are lymphocytes primarily involved in innate immunity and possess important functional properties in antimicrobial and antitumoral response. Our previous work indicated that the Enhancer of Zeste Homolog 2 (Ezh2) is a negative regulator of NK cell early differentiation and function by trimethylation of histone H3 lysine 27 (H3K27me3). Here, we deleted Ezh2 from immature NK and downstream progeny to explore its role in NK cell maturation by single-cell RNA sequencing (scRNA-seq). We identified six distinct NK stages based on transcriptional signature during the maturation of NK cells. Conditional deletion of Ezh2 in NK cells resulted in the maturation trajectory of NK cell arrested in CD11b SP stage 5 which is clustered with genes related to activating function of NK cells. Mechanistically, we speculated that Ezh2 plays a critical role in NK development by activating gene expression of the AP-1 superfamily independent of PRC2 function. Our results implied a novel role for the Ezh2-AP-1-Klrg1 axis to alter NK cell maturation trajectory and NK cell-mediated cytotoxicity.